2017
DOI: 10.1002/qj.3059
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for obtaining wind gusts using Doppler lidar

Abstract: A new methodology is proposed for scaling Doppler lidar observations of wind gusts to make them comparable with those observed at a meteorological mast. Doppler lidars can then be used to measure wind gusts in regions and heights where traditional meteorological mast measurements are not available. This novel method also provides estimates for wind gusts at arbitrary gust durations, including those shorter than the temporal resolution of the Doppler lidar measurements. The input parameters for the scaling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 39 publications
0
55
1
Order By: Relevance
“…Further, the volumetric averaging inherent in the use of lidars means the wind speeds are not directly equivalent to those from in situ anemometry. Nevertheless, vertically pointing Doppler lidars offer the po- tential to quantify wind gusts at heights above those possible from sonic anemometers deployed on meteorological masts (Suomi et al, 2017) and are increasingly being adopted by the wind energy research and operations communities (IEA Wind Task 32 lidar for wind energy deployment) (Clifton et al, 2018). Herein, we evaluate the degree to which the probability distribution of gust amplitudes and GFs derived from the maximum of the disjunct measurements sampled at each of 10 heights (effective duration of ≈ 2 s) in each 10 min period correspond to those from the 18 Hz data from the sonic anemometers.…”
Section: Doppler Lidar Observationsmentioning
confidence: 99%
“…Further, the volumetric averaging inherent in the use of lidars means the wind speeds are not directly equivalent to those from in situ anemometry. Nevertheless, vertically pointing Doppler lidars offer the po- tential to quantify wind gusts at heights above those possible from sonic anemometers deployed on meteorological masts (Suomi et al, 2017) and are increasingly being adopted by the wind energy research and operations communities (IEA Wind Task 32 lidar for wind energy deployment) (Clifton et al, 2018). Herein, we evaluate the degree to which the probability distribution of gust amplitudes and GFs derived from the maximum of the disjunct measurements sampled at each of 10 heights (effective duration of ≈ 2 s) in each 10 min period correspond to those from the 18 Hz data from the sonic anemometers.…”
Section: Doppler Lidar Observationsmentioning
confidence: 99%
“…Cheng et al (2012b) address the development of improved physically-based gusts parametrisations, with an emphasis on the gust profile. Suomi et al (2013Suomi et al ( , 2015Suomi et al ( , 2016Suomi et al ( , 2017 characterise gust profiles using measurements and pursue the development of gust parametrisations in this context. Efthimiou et al (2017b, a) model the underlying wind distribution giving rise to gusts as extreme values, using direct numerical simulation (DNS) and wind tunnel measurements to inform and validate the model, which can be applied at any height, also testing at field sites.…”
Section: New Developmentsmentioning
confidence: 99%
“…Manufacturer Halo Photonics suggests a threshold SNR of −18.2 dB for their StreamLine LiDAR, while tests under quiescent atmospheric conditions suggest a value of −20 dB for the same instrument, resulting in a 40% increase in data availability [34]. In addition, to better estimate the ratio of the wind gust speed to the mean wind speed, Suomi et al [39] suggested using the spike removal technique instead of SNR threshold for data filtering.…”
Section: Measurement Principles and Uncertaintiesmentioning
confidence: 99%